Higher Serum Hepatocyte Growth Factor Concentration is Associated with Better Preservation of GFR in Hemodialysis Patients - Ewa Baum; Beata Maćkowiak; Patrycja Sosińska-Zawierucha; Krzysztof Pawlaczyk; Barbara Kołodziejczak; Andrzej Breborowicz (Karger Publishers, 2017)
Background/Aims: Hemodialysis induces an intravascular inflammatory reaction which may further deteriorate renal function. We studied changes of serum interleukin 6 (IL6) and hepatocyte growth factor (HGF) concentrations during dialysis sessions, and at 12 month intervals. The synthesis of these cytokines in arterial endothelial cells in the presence of serum obtained from dialyzed patients was studied. Changes of the inflammatory reaction during 12 months of treatment were correlated with GFR. Methods: The study was performed on a group of 30 uremic patients treated with hemodialysis. Serum samples were collected before the start of dialysis, 15 minutes, and 4 hours later, when the session was finished. Serum levels of IL6 and HGF were measured with ELISA, as was the effect of serum samples on the synthesis of these cytokines in arterial endothelial cells. Results: At baseline hemodialysis induced an increase of serum IL6 (+10%) and HGF (+164%) levels at the end of the session. After 12 months of treatment predialysis serum IL 6 level was increased as compared to the beginning of the study (+22%), but no change in serum HGF level was observed. At that time the dialysis-induced rise of serum IL6 level was stronger than at the start (+18%), but the observed effect for HGF was weaker (+116%). An inverse correlation was observed between the dialysis-induced increase of HGF level and decrease of GFR after 12 months of study. The same relation was seen for HGF synthesis in the endothelium, but opposite for IL6 synthesis in the endothelium. Conclusions: We found that a higher HGF serum level during hemodialysis treatment is associated with a slower loss of residual renal function.